Climate Change Challenges in Temperate and Sub-Tropical Fruit Tree Cultivation - Petros A. Roussos (Encyclopedia, 2024)
In the last few years, the world has experienced the impacts of climate change, such as elevated mean annual temperature, extreme weather events, drought, etc. Among living organisms, perennial plant species are the ones mostly exposed to climate change impacts, as they may experience different extreme events within the same year, such as flooding during some periods and drought in summer months, extremely low temperatures in winter but excessively high temperatures in summer, etc. Climate change affects a range of physiological functions of temperate fruit and nut tree species, such as their phenophases, bud dormancy release and vernalization, pollination and fruit set, fruit growth and quality, as well as bud sprouting and growth initiation. Besides these, the impact of climate change on pests, diseases, and weeds may generate significant negative interactions with tree physiology, threatening food production, food safety, and human welfare. In the present manuscript, a general aspect of climate change impacts on fruits’ and nut trees’ physiological functions is described and commented on.